PENERAPAN ASAM HUMAT DAN BIOPORI SEBAGAI ALTERNATIF PENGOLAHAN SAMPAH ORGANIK DI SEKOLAH - Nana Misrochah; Chusna, Noor Amalia; Chaerunisa, Natasya Putri (JURNAL PENGABDIAN PAPUA, 2024)
School is a place for intellectual development of students. Efforts to create a healthy school environment affect the comfort and effectiveness of teaching and learning activities so that optimal results will be obtained in terms of cognitive, psychomotor and the formation of attitudes and behavior of students. To realize a healthy school environment, appropriate, planned, integrated, and sustainable efforts are needed, one of which is by managing organic waste in schools. The application of humic acid and biopores as alternatives for processing organic waste in the school environment can bring many benefits, such as reducing the amount of organic waste dumped into the environment, reducing negative impacts on the environment and human health. This community service program is carried out using the Participatory Action Research (PAR) method, namely research carried out in a participatory manner and then applied to action. The target participants of the community service program are grade X students of SMA Ma'arif Karangawen. The activities to be carried out are training and mentoring. Participatory action research used in this community service is an implementation of a theory of biotechnology (utilization of microorganisms) through the development of actions, or several actions to make environmental changes, namely through training and mentoring in making compost using a composter and with appropriate technology in the form of biopores to overcome puddles of water around the SMA Ma'arif Karangawen office. The results of the analysis of participant response questionnaire data showed a positive response from participants of 73% and 27% negative responses, this means that training and mentoring activities for organic waste processing are effectively carried out in schools. Therefore, the application of humic acid and biopores as an alternative to organic waste processing in the school environment is worthy of being implemented and developed further.  Keywords: Humic Acid; biopori ; Participatory Action Research (PAR); limbah organik.